Eye Care Practitioners Are Key Influencer for the Use of Myopia Control Intervention - Yang, Adeline; Pang, Bao Y.; Vasudevan, Pushpaja; Drobe, Björn (Frontiers in Public Health, 2022)
Background: The study sought to investigate the self-reported practices of Singaporean eye care practitioners on myopia management and the interaction between eye care practitioners and parents. Methods: Self-reported questionnaire (1) to eye care practitioners to understand their clinical practice behaviour, their opinion in myopia management (2) to parents on their knowledge of myopia control products and interaction with eye care practitioners. Results: 80.0% of eye care practitioners prescribe myopia control in their practice but only 33.1% of eye care practitioners prescribed myopia control interventions during the first visit, and only 41.4% of parents were recommended myopia control interventions by eye care practitioners, of which 75.6% followed the recommendations of eye care practitioners. Eye care practitioners (53.1%) prefer atropine the most and parents prefer controlling the amount of time doing near work (54.5%) and outdoor activities (52.5%). Eye care practitioners had the highest influence on the choice of vision correction with 78.8% of parents choosing to follow them. 66.9% of eye care practitioners did not prescribe myopia control interventions during the first visit as they lack myopia progression data from the patient. Eye care practitioners felt that more education on myopia control products (57.7%), hands-on workshops (47.7%) and management of children (44.6%) would encourage them to use myopia control interventions more frequently. 40.0% of the eye care practitioners were concerned about the cost of myopia control products. Conclusions: Eye care practitioners strongly influence parents to uptake myopia control interventions. More education and hands-on workshops on myopia and children management can help encourage the use of myopia control interventions by eye care practitioners.